OP0198 Combined effects of tumour necrosis factor inhibitors and nsaids on radiographic progression in ankylosing spondylitis. (12th June 2018) - Gensler, L.S.; Gianfrancesco, M.; Weisman, M.H.; Brown, M.A.; Lee, M.; Learch, T.; Rahbar, M.; Reveille, J.D.; Ward, M.M.
Abstract : Background: The potential of TNFi or NSAIDs to reduce radiographic progression in AS is uncertain and causal effects of both exposures on radiographic progression have not been convincingly demonstrated. In addition, no study has evaluated whether effects are comparable among different NSAIDs in this setting. Objectives: The objective of this study was to explore causal effects of NSAIDs and TNFi on radiographic progression in Ankylosing Spondylitis (AS) and to compare effects of celecoxib to other NSAIDs. Methods: We included all patients meeting the modified New York criteria in a prospective cohort with at least 4 years of clinical and radiographic follow up. Clinical and medication data were collected every 6 months and radiographs were performed at baseline and every 2 years. We used longitudinal targeted maximum likelihood estimation to estimate the causal effect of TNFi and NSAIDs (using the NSAID index) on radiographic progression as measured by the modified Stoke Ankylosing Spondylitis Spine Score (mSASSS) at 2 and 4 years, accounting for time-varying covariates. We controlled for sex, race/ethnicity, education, symptom duration, enrollment year, number of years on TNFi, symptom duration at time of TNFi start, baseline mSASSS, ASDAS-CRP, current smoking, and missed visit status. Results: Of the 519 patients, 75% were male with a baseline mean (SD) age and symptom duration of 41.4 (13.2) and 16.8 (12.5) years respectively. The baseline mean (SD) mSASSS was 14.2 (19.6). At baseline, NSAIDs were used in 66% of patients, of which ½ used an index <50 and ½ an index ≥50). TNFi were used in 46% of patients at baseline. In the setting of TNFi use, the addition of NSAID therapy was associated with less radiographic progression in a dose-related manner at 4 years. When NSAID specific effects were examined, celecoxib in combination with TNFi use was associated with the greatest reduction in radiographic progression and this was significant at both 2 and 4 years (table 1). Conclusions: Dose related use of NSAIDs together with TNFi in AS patients has a synergistic effect in slowing radiographic progression with the greatest effect in those using both high-dose NSAIDs and TNFi. Celecoxib appears to confer the greatest benefit in decreasing progression with effect at both 2 and 4 years. Disclosure of Interest: L. Gensler Grant/research support from: Amgen, AbbVie, UCB, Consultant for: Janssen, Lilly, Novartis, M. Gianfrancesco: None declared, M. Weisman Consultant for: Celltrion, Baylx, Novartis, Lilly, GSK, M. Brown Grant/research support from: Abbvie, Janssen, UCB, Leo Pharma, Consultant for: Abbvie, Janssen, Pfizer, Speakers bureau: Abbvie, UCB, Pfizer, M. Lee: None declared, T. Learch: None declared, M. Rahbar: None declared, J. Reveille Grant/research support from: Lilly UCB, Consultant for: Novartis Janssen Lilly UCB, M. Ward: None declared